A teoria processual e fenomenológica do desenvolvimento na Gestalt-terapia : The processual and phenomenological theory of development in gestalt therapy - de Paulo Bomfim, Leandro (IGT na Rede ISSN 1807-2526, 2026)
Classical theories of human development were organized into normative models describing successive stages, such as those proposed by Freud, Erikson, and Piaget. Although they provided important references for understanding childhood and adulthood, these perspectives tend to universalize life paths and reduce the singularity of experience. Gestalt therapy, in turn, does not present a linear stage-based theory of development but offers a processual and phenomenological understanding centered on the self as an emergent function of the organism–environment field. This article seeks to systematize this proposal, showing how development can be understood through contact, creative adjustment, and the boundaries of the self: organism/environment, self/other, and personality. It argues that human growth in Gestalt therapy is not reduced to adaptation to predefined standards but to expanding the capacity to establish meaningful contacts, integrating bodily, relational, and identity experiences.